Attribution Identification of Runoff Variation in Ganjiang River Basin Based on Budyko Hypothesis - LIU Weilin; HUA Huiling; ZHANG Jingrong; WANG Jun; WANG Yunfei; LIU Lina (Renmin Zhujiang)
The hydrometeorological data of the Ganjiang River Basin for 1953—2017,the non-parametric Mann-Kendall test,and the sliding t test were leveraged to analyze the variation characteristics of the hydrometeorological elements of the study area.Sensitivity analysis of the influencing elements was carried out by the elastic coefficient method on the basis of the Budyko hypothesis,and the influence of each element on the runoff variation in the Ganjiang River Basin was assessed quantitatively.The following observations could be made from the results:① During 1953—2017,the runoff and precipitation in the Ganjiang River Basin showed an insignificant increase trend,and the potential evapotranspiration demonstrated a marked decrease trend.② Runoff variation was positively correlated with precipitation and negatively correlated with the characteristic parameters of the underlying surface and potential evapotranspiration.The runoff in the Ganjiang River Basin was most sensitive to precipitation change.③ Climate change had a positive effect on the increase in the runoff in this Basin,and it was the leading factor affecting runoff variation,with a contribution rate of 73.7%~104.9%.Human activities took the second place,accounting for -4.9%~27.0%.Specifically,human activities had a great impact on the runoff in the upper and middle reaches.The implementation of the ecological construction projects in the upper reaches of the Ganjiang River and the water conservancy construction projects in the middle reaches changed the underlying surface conditions of the basin and thereby affected the river runoff.